(untitled) (ArtCultura, 2010)
A Amazônia desde os tempos iniciais da colonização vem sendo espaço fértil para criação de representações das mais diversas. No século XX literatos e músicos vêm se destacando na construção de imaginários sociais sobre a região. Neste bojo a cultura cabocla é construída/eleita como elemento principal. Pretendemos neste artigo discorrer sobre esse olhar artístico, por vezes quase etnográfico, que músicos e poetas fazem da região amazônica, a partir da produção artística em Belém do Pará no período entre as décadas de 1930 e 1960, fase de efervescência das idéias modernistas na região. Tentaremos assinalar como a intelectualidade artística local ocupa um papel central na construção de imagens regionais, particularmente a partir da música popular, contribuindo para construção de uma tradição musical regional que tem na cultura cabocla e no carimbó a sua base e sustentação. PALAVRAS-CHAVE: música amazônica; literatura amazônica; música cabocla, carimbó. ABSTRACT: The Amazonian has been a fertile space for creation of representation of the most several since the begining of the colonization. In the XX century, writers and musicians have became highlighting in the constructions of social imaginary on the area. In this salience, the cabocla culture is built/chosen as principal element. We intend in this article to discourse about that artistic glance, almost ethnographic, that musicians and poets make about the Amazon region, starting with the artistic production in Belém of Pará during the 1930 and 1960 years, phase of effervescence of modernist ideas in this area. We’ll try to mark how the local artistic intellectuality ocupies the central paper in the construction of regional images, particularly starting from the popular music, contributing then to the construction of a regional musical tradition, that has its base and sustentation in the carimbó and in the cabocla culture. KEYWORDS: amazon music; amazon literature; cabocla music; carimbó.